Kepemimpinan Transformasional, Kompensasi Finansial, dan Lingkungan Kerja: Menelusuri Pengaruhnya terhadap Turnover Intention pada Klinik Dina Akupuntur & Beauty Care di Surabaya & Sidoarjo - Evan Aprillio, Dandy; Nugroho, Rusdi Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of technology in the digital era has significantly impacted human resource management (HRM), particularly concerning the high employee turnover that is a primary concern in HRM. This research explores the influence of factors such as transformational leadership, financial compensation, and work environment on employees' turnover intention, aiming to assist companies in designing effective strategies to retain quality employees amidst dynamic market changes. The research object is Dina Acupuncture & Beauty Care Clinic in Surabaya & Sidoarjo. This research involves the entire population of Dina Acupuncture & Beauty Care Clinic in Surabaya & Sidoarjo, totaling 60 individuals. Data collection is carried out using both primary and secondary methods, incorporating interviews, questionnaires, and literature reviews. The research methodology employed is quantitative. Data analysis employs multiple linear regression techniques, and a Likert scale is utilized for sampling. Analytical tests encompass validity, reliability, normality, multicollinearity, heteroskedasticity, F-test, and t-test. Furthermore, data processing is conducted using SPSS software version 25. The research results indicate that the t-test produces a t-value of -3.548 for transformational leadership, which is smaller than the critical t-value of -2.003. Meanwhile, for financial compensation, the t-value is 5.392, exceeding the critical t-value of 2.003. Similarly, for the work environment, the t-value is -4.538, which is smaller than the critical t-value of -2.003. All variables exhibit significance below 0.05. Partially, transformational leadership and the work environment have a significant negative influence on turnover intention. On the other hand, financial compensation has a significant positive impact on turnover intention. The F-test yields an F-value of 23.775, surpassing the critical F-value of 2.77, with a significance of 0.000 < 0.05. This indicates that collectively, transformational leadership, financial compensation, and the work environment significantly influence turnover intention. Based on the results of this research, it can be concluded that independent variables, such as transformational leadership and the work environment, partially have a significant negative impact on the dependent variable, namely employee turnover intention. Meanwhile, financial compensation partially has a significant positive influence on turnover intention. Collectively, the independent variables, including transformational leadership, financial compensation, and the work environment, significantly affect the dependent variable, namely turnover intention. This conclusion indicates that these factors play a crucial role in understanding and managing employees' tendencies to leave their jobs. Therefore, when developing company strategies and policies, it is essential to consider these aspects to enhance employee retention and achieve organizational goals more effectively.